External pancreatic secretion after bombesin infusion in man. Issue 12 (December 1975) - Basso, N; Giri, S; Improta, G; Lezoche, E; Melchiorri, P; Percoco, M; Speranza, V
Abstract : The effect of bombesin on external pancreatic secretion was studied in seven healthy volunteers and intwo patients with a two-thirds gastrectomy and a pancreatic fistula. After bombesin infusion (15 ng/kg/min), gastrin levels were significantly raised in all volunteers, but remained at basal levels in the gastrectomized patients. Bombesin was effective in stimulating pancreatic secretion in all patients. The volume of secretion increased tow-fold when compared with basal volume. Amylase and trypsin concentrations and outputs in the duodenal juice were greatly agumented (amylase concentration: basal, 70 dye U/ml; post-bombesin, 620 dye U/ml. Amylase output: basal, 1000 dye U/15 min; post-bombesin, 15, 800 dye U/15 min). Secretin, when administered in conjunction with bombesin, partially inhibited its secretory effect. Bicarbonate secretion was slightly stimulated by bombesin, but at a very low level. A similar pattern of results was obtained in the two gastrectomized patients. In man, bombesin exerts an effect on pancreatic secretion that mimics the effect of CCK-PZ, thus confirming the results obtained in the experimental animal. Gastrin does not play a fundamental role in this phenomenon.